2006
DOI: 10.1093/jn/136.5.1323
|View full text |Cite
|
Sign up to set email alerts
|

Intake of Fermented Soybeans, Natto, Is Associated with Reduced Bone Loss in Postmenopausal Women: Japanese Population-Based Osteoporosis (JPOS) Study

Abstract: Japanese fermented soybeans (natto in Japanese), which contain a large amount of menaquinone-7, may help prevent the development of osteoporosis. We assessed the possibility of an association between habitual natto intake and bone mineral density (BMD) and BMD change over time in healthy Japanese women who participated in a large representative cohort study (Japanese Population-based Osteoporosis Study: JPOS study). The BMD was measured at the spine, hip, and forearm in 944 women (20-79 y old) at baseline and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
87
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(92 citation statements)
references
References 31 publications
4
87
0
1
Order By: Relevance
“…The intake frequency of milk and dairy products, Ikeda et al showed that calcium intake and the amount of natto, tofu, and other soybean products consumed was higher among postmenopausal women than among premenopausal women, and intake of calcium and soybean products was higher at follow up than at baseline for healthy Japanese women Ikeda et al, 2006 . Women who had consumed more milk and dairy products and soybean products might have been aware of their benefits with respect to bone health.…”
Section: Characteristics Of Respondentsmentioning
confidence: 99%
“…The intake frequency of milk and dairy products, Ikeda et al showed that calcium intake and the amount of natto, tofu, and other soybean products consumed was higher among postmenopausal women than among premenopausal women, and intake of calcium and soybean products was higher at follow up than at baseline for healthy Japanese women Ikeda et al, 2006 . Women who had consumed more milk and dairy products and soybean products might have been aware of their benefits with respect to bone health.…”
Section: Characteristics Of Respondentsmentioning
confidence: 99%
“…By contrast, in Japan the intake of natto in some regions provides a high intake of MK-7 [20]. A population-based study in Japan showed a positive association between natto intake and BMD in the femoral neck in post-menopausal women [21], and it has been postulated that supplementation of the Western diet with MK-7 might prevent osteoporosis [22].…”
Section: Introductionmentioning
confidence: 99%
“…One explanation may be that the Japanese consume natto, a food very rich in menaquinone-7 (K2). 13 In conclusion, uremic hemodialysed patients may present serious complications when treated with coumarin-derived anticoagulants. The main complications are hemorrhage, increased risk for bone fracture, and a high prevalence of arterial calcifi cation with calciphylaxis.…”
Section: Discussionmentioning
confidence: 97%